Young people and domestic violence national research on young people's attitudes and experiences of domestic violence. (Attorney-General's Dept., 2001)
"This research project surveyed young people's experiences of, and attitudes towards, domestic violence. It is the largest piece of research of its kind ever conducted in Australia. Given the subjective, personal and sensitive nature of this topic the investigation involved gathering quantitative and qualitative data. The research was designed to allow these two forms of data to be used in developing a comprehensive picture of young people's experience. The chief research aim was to provide national data on young people's attitudes to, and experience of, domestic violence. The final report constitutes a synthesis and summary of the research findings. This report contains an introduction, a literature review, details of the qualitative research, the findings from the quantitative research and a section on interpretation of the results and implications for policy and communication."--Full report, p. xiv.